To evaluate efficacy of FNAC in diagnosis of cystic lesions in paediatric age group patients- A retrospective study in a tertiary care teaching hospital - Dr. Rashmi Nichlani; Dr. Nitin Rohira; Dr. Reena Verma; Dr. Nitin Verma (Tropical Journal of Pathology and Microbiology, 2018)
Introduction: Fine Needle Aspiration Cytology is a rapidand economical mode of preoperative diagnosis. It has early availability of results & simple procedure with minimal trauma and complications but it has limited literature in pediatric age group and cystic lesions with and remains an area which needs more light.Objective: To evaluate the role of fine needle aspiration cytology as a diagnostic tool for cystic lesions in paediatric patients of age up to 12 years.Methods: A retrospective study was undertaken toevaluate efficacy of FNAC in diagnosis of cystic lesions in paediatric age group patients of age upto 12 years presenting in the department of pathology of a tertiary care teaching hospital. Case sheets for 2 years study duration were studied and analysed for data. Common age group, male: Female, commonest site, commonest diagnosis as benign & malignant lesion were study parameters along with positive predictive value, sensitivity & specificity. Results 105 cases were reported in a period of 2 years, out of which 17.14% were reported from age group 01 month-04 years, 58.09% in 04-08 years & rest 24.76% were reported in 08-12 years age group.60.95% of patients were female. Commonest site was head & neck (86.66%) followed by abdomen (5.71%), extremities (3.80%) chest & pelvis (1.90% each). Commonest diagnosis was chronic inflammatory cysts (32.38%), followed by benign cysts (27.6%), acute inflammatory lesions (15.23%) acquired cysts (12.38%), developmental cysts (10.47%) & malignant cysts in 1.90%.Conclusion: FNAC is an efficacious diagnostic tool with high sensitivity & specificity and minimal safety concerns.It is showing to be equally promising in diagnosis of cystic lesions in paediatric age.